Nanoscale phase separation in DSPC-cholesterol systems - Brown, Angela C (Langmuir : the ACS journal of surfaces and colloids, 2013)
The lipid arrangement of eukaryotic cell membranes has been shown to be heterogeneous, with domains enriched in cholesterol and saturated phospholipids, coexisting with a continuous phase that is enriched in unsaturated phospholipids. While the existence of these domains is well-established, there is still a lack of consensus regarding domain size and the factors influencing it. In this work, we investigate model membranes consisting of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC)-1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC)-cholesterol (Chol) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC, 18:1-16:0)-DSPC-Chol with a steady-state fluorescence assay and report the influence of phospholipid chain saturation and chain length on domain size. The spectral shifts of 1-myristoyl-2-[12-[(5-dimethylamino-1-naphthalenesulfonyl)amino]dodecanoyl]-sn-glycero-3-phosphocholine (DAN-PC) and a Förster resonance energy transfer (FRET) assay were used, along with an analytical model, to estimate domain sizes. A region of nanoscale domain existence was observed in both ternary systems; however, the domains formed in the system containing the asymmetric lipid (POPC, 18:1-16:0) were larger than those formed in the diunsaturated lipid (DOPC, 18:1-18:1). This is a new finding, as domains were not previously known to exist in similar POPC-based systems